Afterword: how we argue. Issue 2 (1st February 2023) - Swoboda, Jessica
ABSTRACT: By insisting that only one method – critique or postcritique – can prove victorious, the 'method wars' in literary studies have brought out the worst in literary scholars: the inclination to dismiss arguments that conflict with one's own, the unwillingness to take seriously positions that challenge a person to question theirs, and the felt need to fight for intellectual superiority. As a result, literary scholars fight not against the neoliberal forces stripping the discipline of resources but with each other over whose claims about why literary studies matters are more convincing. The wager of this afterword is that both the present and future of literary studies depend on intellectual solidarity and collective action; how we argue bears on our future because it impacts our ability to forge collectives.